The study of compound nouns in the dictionary - SYSOUPHANH, Sangkhome; DUANGCHAN, Boy; SONETHALA, Amphai; INVANHKHAM , Maiphone; CHANHTHAHONG, Khamxay (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The objective of this research is to analyze the structure and characteristic meaning of compound nouns in the dictionary of Dr. Thongkham Onmanisone. The research applied the following Methodologies to analyze the compound word: taking the compound nouns to analyze their structure and their meaning by using the meaning of those compound nouns to identify in linguistic characteristics. The findings of this research displayed that there are 606 compound nouns which is a structure of compound nouns (noun + noun) including 419 words; equaled 69.14%. The least compound words' structure was verb plus adverb; equaled 0.16% and adverb plus noun; equaled 0.16%. For the meaning part, the compound nouns are divided into two types such as direct compound nouns and indirect compound nouns. From grouping, these two types of compound nouns according to their linguistic and cultural characteristics found that there were 452 direct compound nouns. There were 239 compound nouns in the most natural vocabulary which equal 52.85 percent. There were 25 direct compound nouns of the vocabulary in intellectual, mood, and value equaled 5.51%. from 160 indirect compound nouns found 98 indirect compound nouns in the most vocabulary of nature equaled 61.24 percent. The least was indirect compound nouns in the vocabulary of intellectual, mood, and value which was 18 words; equaled 11.24%.